Transaminase enzymes and lipid profiles and histological changes in Wistar rats after administration of bintangur (Calophyllum soulattri) leaves ethanolic extract - INARAH FAJRIATY; PRATIWI APRIDAMAYANTI; SUCI PUTRI RAHMAWANI; ABDURRACHMAN ABDURRACHMAN (Smujo International, 2018)
Fajriaty I, Apridamayanti P, Rahmawani SP, Abdurrachman. 2018. Transaminase enzymes and lipid profiles and histological changes in Wistar rats after administration of bintangur (Calophyllum soulattri) leaves ethanolic extract. Nusantara Bioscience 10: 27- 35. Bintangur (Calophyllum soulattri Burm. F) can be found in West Kalimantan and traditionally used as a medicine for treatment of wounds, inflammation, and rheumatism. Bintangur contains terpene derivatives, xanthones, coumarins, steroid derivatives, flavonoid and also saponins. The present study was conducted to determine the in vivo effect of oral administration of bintangur leaves ethanolic extract (BLEE) on transaminase and lipid profiles and histological changes in experimental rats. Eighty-four Wistar rats were divided into six groups; each group consisted of seven male and seven female rats. The first group was applied with CMC-Na 1% as a control. The second, third, and fourth group were applied with 100 mg kg-1 BW, 400 mg kg-1 BW, 1000 mg kg-1 BW dose of BLEE respectively. The fifth and sixth group were the satellite for assessment of reversibility, persistence or delayed effects. The animals were given extract once daily for 28 days, while for the satellite groups still observed until 14 days. At the end of the study, all rats were sacrificed, and the blood and organs were collected for biochemical and histological examination. The result showed that BLEE increased transaminase profile, ALT, and AST, with the highest increase in 400 mg kg-1 BW dose. But a significant increase (p<0.05) only found in AST profile of 400 mg kg-1 BW dose in female rats. In lipid profile, BLEE did not affect cholesterol total, but caused significant decrease (p<0.05) in triglyceride profile of 1000 mg kg-1 BW dose in male and female rats. In the histological assessment, obvious histological changes were observed in liver and heart. There had necrosis of hepatocytes cells of male and female rats with obvious changes in 1000 mg kg-1 BW dose and congestion of central vein of male rats in 400 mg kg-1 BW dose and 1000 mg kg-1 BW dose. In heart muscle fibers showed an irregular structure in 1000 mg kg-1 BW dose of female rats. While observation of spleen showed no harmful changes in all groups. The conclusion of this study showed BLEE increase transaminase profile and some damaging effect on the liver and heart organ of Wistar rat but should be considered as an herbal medicine with potential effect as antihypertriglyceridemia.